Rizal’s Legacy for the 21st Century: Progressive Education, Social Entrepreneurship and Community Development in Dapitan - Quibuyen, Floro (Social Science Diliman: A Philippine Journal of Society and Change; Vol 7 No 2 (2011), 2012)
Rizal’s four years in Dapitan have not been fully explored for the light they can shed on contemporary issues in community development and education. In particular, the significance of the school he founded in Talisay has not merited scholarly commentary. Those fruitful four years in Dapitan have become Rizal’s most unappreciated legacy, yet they are precisely what make Rizal singularly relevant to the 21st century. This essay explains why.
Keywords: Dapitan, Talisay, progressive education, community development, social entrepreneurship, Jose Rizal